Semantic Support for Scenarios to Improve Communication in Agribusiness - Antonelli, Rubén Leandro (2019)
Organizations produce and exchange a huge amount of critical information, which main purpose is to obtain acceptable results. Hence, the trend is by considering integrated systems that can be easily adapted to several domains, especially when they need to exchange information. In this context, the agribusiness sector is a good example where massive data is generated, which implies the need for information sharing and collaboration, where the great challenged is support and understand the colliding context. However, every software system relies on its context, with its own rules, dynamism, and languages. Hence, it implies a significant effort to have a complete under- standing of the composed domain. For this purpose, scenarios are well-known tools to describe dynamic domains and are commonly described under text- based context. When different stakeholders build Scenarios, it is essential to review them in order to unify their description. Thus, Scenarios under this unified perspective will better support the analysis and identification of rela- tionship between two or more domains. This analysis is the key to design mechanisms to exchange information. Therefore, in the light of this, this paper proposes a semantic definition of Scenarios and a set of queries to identify issues in the Scenarios and improve their quality. In addition to this, a wiki platform to implement the semantic support and the queries is also provided.